2012
DOI: 10.4088/jcp.12m07693
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Differences Between Pregnancy-Onset and Postpartum-Onset Major Depressive Disorder

Abstract: Women with a history of perinatal and nonperinatal major depression are more likely to relapse during pregnancy than postpartum, a finding that points to the need for closely monitoring these women for depression during pregnancy. In addition, these findings of differences in risk factors and clinical features suggest that postpartum-onset major depression may have a pathophysiology distinct from major depression that begins during pregnancy. Time of onset of perinatal depression should be considered in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 0 publications
1
38
0
2
Order By: Relevance
“…In our study, we used the criteria of six months postpartum to define PPD. Consistent with previous findings, our results show the majority (84%) of postpartum MDE occur within six weeks after childbirth (Kettunen et al, 2014) and up to 94% of postpartum MDE occur within the first 4 months postpartum (Altemus et al, 2012). This indicates the closer to the time after childbirth, the higher the risk is for developing episodes of PPD (Banti et al, 2011;Cox et al, 1993;Munk-Olsen et al, 2006;Stuart et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we used the criteria of six months postpartum to define PPD. Consistent with previous findings, our results show the majority (84%) of postpartum MDE occur within six weeks after childbirth (Kettunen et al, 2014) and up to 94% of postpartum MDE occur within the first 4 months postpartum (Altemus et al, 2012). This indicates the closer to the time after childbirth, the higher the risk is for developing episodes of PPD (Banti et al, 2011;Cox et al, 1993;Munk-Olsen et al, 2006;Stuart et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Studies show that women with MD identified during the postpartum period comprise a heterogeneous group (Altemus et al, 2012;Zaconeta et al, 2013). Cooper and Murray (1995) reported first-onset postpartum MDE predicted further postpartum depressive episodes but not non-postpartum depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Of women who have major depression postpartum, approximately one quarter have chronic depression, one third have depression that onset during pregnancy and only a little more than one third have actual postpartum onset of depression (Wisner et al, 2013). Compared to women with postpartum onset of major depression, women who have onset of major depression during pregnancy are more likely to have a prior history of depression, and history of typical risk factors for depression including abuse and low social support (Stowe et al, 2005; Altemus et al, 2013). Findings from a hormonal challenge study conducted in healthy parturient women with no history of postnatal depression and a comparison group with a history of postpartum depression suggests that with exposure to and withdrawal of pregnancy levels of estradiol and progesterone, there are subset of women who are particularly vulnerable to develop depression (Bloch et al, 2000).…”
Section: Sex Differences In Mood Disordersmentioning
confidence: 99%
“…This change reflects the finding that a proportion of “postpartum” depressive episodes actually begin during pregnancy and continue and often worsen during the postpartum [14] and emphasizes the importance of managing mood disorders both during and after pregnancy. [5] However, some authors have pointed out that the combination of prenatal and postnatal onset in a single specifier may obscure important differences in the epidemiology, [15] clinical presentation, [16-18] prognosis [19] and treatment response [5] of major depression in these two periods.…”
mentioning
confidence: 99%
“…In contrast, psychomotor symptoms (restlessness/agitation), [8] impaired concentration/decision making [8] and anxiety symptoms [11, 20] may be more prominent in peripartum depression. In addition, depressive episodes with postpartum onset may be more often associated with obsessive-compulsive and psychotic symptoms than those with pregnancy-onset [16] and prior research supports differences in depression symptom levels from pregnancy to postpartum. [33, 34] …”
mentioning
confidence: 99%